Les mesures d'austérité et les femmes: analyse des documents budgétaires depuis novembre 2008 - Couturier, Eve-Lyne; Tremblay-Pépin, Simon; Institut de recherche et informations socio-économiques (IRIS, 2015)
Contrairement à ce que défend le gouvernement du Québec, celui-ci mène actuellement des politiques d'austérité. Ces politiques ont croisé un certain nombre de mesures de relance que le Québec a tenté d'établir depuis la crise de 2008, mais il n'en demeure pas moins que les compressions ont été plus importantes que les investissements. Cette étude montre que si les mesures de relance ont d'abord favorisé les hommes, les mesures d'austérité, quant à elles, ont surtout affecté les femmes. Ces dernières se trouvent donc doublement perdantes vis-à-vis des mesures instaurées par le gouvernement québécois depuis la crise. Si elle diffère en termes de degré, cette situation correspond à celle qu'on a pu observer en Europe lors de la mise en place de mesures d'austérité.
disponible gratuitement à https://iris-recherche.qc.ca/wp-content/uploads/2021/03/Femmes_et_austerite_WEB.pdf
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; austérité; canada; capitalisme; cours; discipline; histoire et politique; inégalités; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; sofia; systèmes d'oppressions; thématiques; travail; violences

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques